SISTEM PAKAR UNTUK MENGETAHUI PERKEMBANGAN MOTORIK NORMAL PADA ANAK MENGGUNAKAN METODE CERTAINTY FACTOR (CF) - Sawitri Latipah (STMIK YADIKA BANGIL, 2020)
Abstract: There are some parents who do not know about how their children grow, so sometimes there are parents who force their children in various ways so that they can grow like children around them. But there are also parents who are more concerned with the wishes of children by allowing children to grow as they occur. With that, this research will build a system in which children are declared normal or abnormal growth by answering a number of questions through an application with website access. So that it can help parents better know what is happening to their child's growth and development. This study uses the certainty factor (CF) method as a reference calculation, with several possibilities, namely very sure, sure, quite sure, a little sure, not sure and not sure. With these parameters will be calculated the value of confidence weights with the weight of symptoms so as to produce diagnostic results in the form of a percentage value. In this study, for example if the user chooses the weight of certainty, the diagnostic result obtained is 97.33%, meaning that the user has gross motor growth / normal physical movement. Keywords: Sistem Pakar, Certainty Factor (CF), Motorik